2014
DOI: 10.3390/coatings4030587
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Photocatalytic Activity of Anatase TiO2 Thin Films by Modifying the Preferred <001> Grain Orientation with Reactive DC Magnetron Sputtering

Abstract: Anatase TiO 2 thin films were deposited by DC reactive magnetron sputtering on glass substrates at 20 mTorr pressure in a flow of an Ar and O 2 gas mixture. The O 2 partial pressure (P O2 ) was varied from 0.65 mTorr to 1.3 mTorr to obtain two sets of films with different stoichiometry. The structure and morphology of the films were characterized by secondary electron microscopy, atomic force microscopy, and grazing-angle X-ray diffraction complemented by Rietveld refinement. The as-deposited films were amorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…After deposition the films were post-annealed for 1h at 500 o C in air (Figure 1b). 22 To exclude the possibility of any influence of target history on ensuing film properties, two different sets of Ti targets were employed: one set of two new targets and another set which had been extensively used and hence exhibited clear "racetrack" features. 25 Film thicknesses were between 573 and 696 nm, as determined by surface profilometry (Dektak XT Advance, Bruker).…”
Section: Experimental Part and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After deposition the films were post-annealed for 1h at 500 o C in air (Figure 1b). 22 To exclude the possibility of any influence of target history on ensuing film properties, two different sets of Ti targets were employed: one set of two new targets and another set which had been extensively used and hence exhibited clear "racetrack" features. 25 Film thicknesses were between 573 and 696 nm, as determined by surface profilometry (Dektak XT Advance, Bruker).…”
Section: Experimental Part and Methodsmentioning
confidence: 99%
“…18 We have previously demonstrated that the preferential <001> orientation of the crystal grains in nanostructured films can be controlled by altering the partial oxygen pressure in the deposition chamber during thin-film preparation. [22][23] In this work we systematically vary the fraction of {001} planes in anatase TiO 2 films and show that their photo-reactivity follows a quadratic functional dependence as a function of exposed {001} surface area. Apart from providing experimental quantification of facet reactivity, our results can be used to predict photocatalytic reaction rates from structural properties of nanostructured TiO 2 materials.…”
mentioning
confidence: 97%
“…Reactive magnetron sputtering is realized in magnetron sputtering with a reactive gas (such as oxygen or nitrogen) introduced into the vacuum chamber, in addition to an inert working gas [8][9][10][11][12]. There are several reactive magnetron sputtering techniques, i.e., direct current reactive magnetron sputtering (DCRMS) [10], pulsed reactive magnetron sputtering (PMS) [11], radio frequency reactive magnetron sputtering (RFRMS) [12] and medium frequency reactive magnetron sputtering (MFRMS) [9], which are ordered according to the frequency of the power supply of the sputtering target.…”
Section: Introductionmentioning
confidence: 99%
“…There are several reactive magnetron sputtering techniques, i.e., direct current reactive magnetron sputtering (DCRMS) [10], pulsed reactive magnetron sputtering (PMS) [11], radio frequency reactive magnetron sputtering (RFRMS) [12] and medium frequency reactive magnetron sputtering (MFRMS) [9], which are ordered according to the frequency of the power supply of the sputtering target. The disadvantages of DCRMS are target poisoning and arc problems, and the prepared films often have large embedded particles, which renders the deposition processes hard to control and reproduce [13]; the demerits of RFRMS are the high-cost of equipment and low deposition rates [14]; thus neither of these two techniques is suitable for the preparation of high quality thin films and coatings at an industrial level.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, 1‐D nanorod structures have been actively studied for photovoltaic applications due to their faster charge transport and lower rate of electron‐hole recombination than other nanostructures . Furthermore, several processing methods have been explored to generate various shapes and morphologies of TiO 2 nanostructure . Among these, solution‐based processes such as chemical bath deposition (CBD) and hydrothermal process not only require small capital investment on equipment, but are also proceeded with a low temperature process that benefits certain applications using temperature‐sensitive substrates.…”
Section: Introductionmentioning
confidence: 99%